Molybdenum-induced endogenous nitric oxide (NO) signaling coordinately enhances resilience through chlorophyll metabolism, osmolyte accumulation and antioxidant system in arsenate stressed-wheat (Triticum aestivum L.) seedlings. (1st January 2022) - Alamri, Saud; Siddiqui, Manzer H.; Mukherjee, Soumya; Kumar, Ritesh; Kalaji, Hazem M.; Irfan, Mohammad; Minkina, Tatiana; Rajput, Vishnu D.
Abstract: There is little information available to decipher the interaction between molybdenum (Mo) and nitric oxide (NO) in mitigating arsenic (As V ) stress in plants. The present work highlights the associative role of exogenous Mo and endogenous NO signaling in regulating As V tolerance in wheat seedlings. Application of Mo (1 μM) on 25-day-old wheat seedlings grown in the presence (5 μM) or absence of As V stress caused improvement of photosynthetic pigment metabolism, reduction of electrolytic leakage and reactive oxygen species (ROS), and higher accumulation of osmolytes (proline and total soluble sugars). The molybdenum treatment upregulated antioxidative enzymes, such as superoxide dismutase, ascorbate peroxidase and glutathione reductase. In addition, the accumulation of nonenzymatic antioxidants (ascorbate and glutathione) was correlated with an increase in ascorbate peroxidase and glutathione reductase activity. The application of cPTIO (endogenous NO scavenger; 100 μM) reversed the Mo-mediated effects, thus indicating that endogenous NO may accompany Mo-induced mitigation of As V stress. Mo treatment stimulated the accumulation of endogenous NO in the presence of As V stress. Thus, it is evident that Mo and NO-mediated As V stress tolerance in wheat seedlings are primarily operative through chlorophyll restoration, osmolytes accumulation, reduced electrolytic leakage, and ROS homeostasis. Graphical abstract: Schematic model for the synergistic role of Mo and NO in mediating tolerance to arsenic stress in wheat seedlings. Exogenous supply of Mo induced nitric oxide signaling that up-regulated Chlorophyll metabolism, osmolyte accumulation and triggered antioxidative defense system. Image 1 Highlights: Arsenate (As V ) toxicity impairs photosynthesis and chlorophyll (Chl) metabolisms. Molybdenum (Mo) induces nitric oxide (NO) signaling in As V -stressed wheat seedlings. Exogenous Mo and endogenous NO regulate Chl and photosynthesis metabolisms. Mo and NO triggers nitrogen and proline metabolism under As V toxicity. NO provides more efficacy to Mo to alleviate As V toxicity in wheat seedlings.